Climate change adaptation and mitigation in agriculture: a review of the evidence for synergies and tradeoffs - Barbieri, Lindsay; Bittner, Carolyn; Wollenberg, Eva; Adair, E Carol (Environmental research letters, 2024)
Agricultural practices that both support climate change mitigation and facilitate adaptation to a changing climate are critical for reducing greenhouse gas emissions while ensuring food security. This need has led to many claims regarding the potential for a variety of agricultural practices to achieve synergies between mitigation and adaptation in agriculture. However, the evidence for climate change mitigation and adaptation synergies in agriculture remains mixed. To evaluate such claims, we examined the evidence for these synergies by conducting a systematic review of peer-reviewed literature that make claims about outcomes for both climate change adaptation and mitigation in agriculture. Based on 87 articles identified, we show that synergistic outcomes are claimed more frequently than tradeoffs for all practices, yet the evidence was stronger for mixed and conflicting outcomes than for synergies. Indeed, claims of synergistic outcomes may be overstated, because these publications more often relied on secondary data rather than empirically evaluating adaptation and mitigation outcomes. We also show important gaps in the consideration and assessment of climate change adaptation and mitigation objectives and outcomes. This review highlights the critical need for more robust research, evidence, and evaluation of the adaptation and mitigation outcomes of agricultural practices, and the need to clarify the contexts of such results, in order to effectively support policies and practices that aim to promote synergistic outcomes and avoid conflicting outcomes.